Screening parameters on the biological active compounds of coffee bean mixed with nigella sativa - Goh, Ke Pei (2016)
The addition of Nigella sativa to coffee offers consumers to gain health benefits besides reducing the components which are bad to health. This research aimed to investigate the effect of significant parameters of coffee bean mixed with Nigella sativa in terms of biological compounds. The parameters studied included temperature, ratio of coffee to Nigella sativa and mixing time. The biological compounds included caffeine, total phenolic content and antioxidant activity. Design Expert was used to screen the parameters of the above factors. UV-VIS spectrophotometer was mainly used to measure the total phenolic content and antioxidant activity. From the screening process, three parameters which were temperature, ratio of Nigella sativa to coffee and mixing time contributed a significant effect to the caffeine content analysis for both black and white coffee with the P value<0.05. Interaction was found between temperature and ratio of Nigella sativa to coffee. As for total phenolic content, all three parameters(temperature, ratio of Nigella sativa to coffee and mixing time) contributed significant effects to the overall results for black coffee with P value< 0.05. Significant interactions between temperature and ratio of Nigella sativa to black coffee and between ratio of Nigella sativa to black coffee and mixing time. On the other hand, only ratio of Nigella sativa to coffee and mixing time resulted to significant contribution to the total phenolic content of white coffee. For antioxidant activity, only two parameters contributed significant effects for the results for both coffee. For black coffee, they were temperature and mixing time with P value<0.05. However, interaction was found between temperature and ratio of Nigella sativa to coffee. Whereas, ratio of Nigella sativa to coffee and mixing time significantly affected the antioxidant activity of white coffee with P value<0.05. The results showed that Nigella sativa worked better with black coffee than white coffee. All parameters were significant to black coffee, only two parameters played significant roles to white coffee. The parameters were ratio of Nigella sativa to coffee and mixing time. As a conclusion, the additional of Nigella sativa to the coffee had improved the quality of coffee by reducing the caffeine content and increasing the total phenolic content and antioxidant activity of coffee.